Portrayal of the 20th century woman as seen through Edith and Clarissa in Anita Brookner’s Hotel du Lac and Virginia Woolf’s Mrs. Dalloway - Tabassum, Sazerin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2023.